The relevance of awareness on the nutritional value of Chatime's Milk Tea to the buying decisions of college students at SM Manila Branch - Bayot,Rethel Anne Chezka M. Anonuevo, Ma. Krizza Joyce R. Billones,Jayson Carl O. Paras, Luis yves R. Pascual, Catherine Venice P. and Rualo,Julienne Erika A. 4 0 16; 5 (2012)
u
Research Paper: (BSBA major Marketing Management) - Pamantasan ng Lungsod ng Maynila 2012.
Keywords: 2 -- 0; 6; 20; 20; 2